Interactive multimedia: Enhacing students’ cognitive learning and creative thinking skill in Arthropod material - Ubung Darmawan; Sri Redjeki; W. Widhorini (University of Muhammadiyah Malang, 2020)
Interactive multimedia based on Adobe Director, as a learning medium, is important in optimizing students’ learning outcomes. This study aimed to develop interactive multimedia in Arthropod topic as a learning media based on Adobe Director in optimizing students’ cognitive learning outcomes as well as their creative thinking skills. This Research and Development (R & D) adopted Lee and Owens model. The validity of the media developed was assessed by material and media experts. The product trial was done by involving ten of X graders. The students' cognitive learning outcomes and creative thinking skills were measured using pretest and posttest. The data obtained were then analyzed using N-gain calculation. The results showed that the interactive multimedia based on Adobe Director was categorized as feasible (based on material expert) and very feasible (based on media expert). The N-gain scores of cognitive learning outcomes of C1, C2, C3, C4 were 0.70, 0.75, 0.71, and 0.56 respectively. Moreover, the N-gain scores of creative thinking skills were 0.55 (widening), 0.43 (connecting), and 0.73 (reorganizing). It can be concluded that the interactive multimedia based on Adobe Director developed is feasible and able to improve cognitive learning outcomes and students' creative thinking skills.